Stimulatory MAIT cell antigens reach the circulation and are efficiently metabolised and presented by human liver cells. Issue 12 (20th January 2022) - Lett, Martin J; Mehta, Hema; Keogh, Adrian; Jaeger, Tina; Jacquet, Maxime; Powell, Kate; Meier, Marie-Anne; Fofana, Isabel; Melhem, Hassan; Vosbeck, Jürg; Cathomas, Gieri; Heigl, Andres; et al.
Abstract : Objective: Mucosal-associated invariant T (MAIT) cells are the most abundant T cells in human liver. They respond to bacterial metabolites presented by major histocompatibility complex-like molecule MR1. MAIT cells exert regulatory and antimicrobial functions and are implicated in liver fibrogenesis. It is not well understood which liver cells function as antigen (Ag)-presenting cells for MAIT cells, and under which conditions stimulatory Ags reach the circulation. Design: We used different types of primary human liver cells in Ag-presentation assays to blood-derived and liver-derived MAIT cells. We assessed MAIT cell stimulatory potential of serum from healthy subjects and patients with portal hypertension undergoing transjugular intrahepatic portosystemic shunt stent, and patients with inflammatory bowel disease (IBD). Results: MAIT cells were dispersed throughout healthy human liver and all tested liver cell types stimulated MAIT cells, hepatocytes being most efficient. MAIT cell activation by liver cells occurred in response to bacterial lysate and pure Ag, and was prevented by non-activating MR1 ligands. Serum derived from peripheral and portal blood, and from patients with IBD stimulated MAIT cells in MR1-dependent manner. Conclusion: Our findings reveal previously unrecognised roles of liver cells in Ag metabolism and activation of MAIT cells, repression of which creates an opportunity to design antifibrotic therapies. The presence of MAIT cell stimulatory Ags in serum rationalises the observed activated MAIT cell phenotype in liver. Increased serum levels of gut-derived MAIT cell stimulatory ligands in patients with impaired intestinal barrier function indicate that intrahepatic Ag-presentation may represent an important step in the development of liver disease.